Interesting electrophysiological phenomenon during positioning of the lead deep inside the septum - Jiabo Shen; Longfu Jiang; Hao Wu; Lifang Pan (Annals of Noninvasive Electrocardiology, 2022)
Abstract Left bundle branch pacing (LBBP) is a developing physiological pacing technique. Wu et al. proposed that direct LBB capture could be confirmed by recording retrograde His potential (PoReHis) and mapping of the left conduction system potential. The transventricular‐septal electrophysiological phenomena deserve further study. Here, we used a continuous uninterrupted pacing technique to confirm the LBB capture by dynamically observing changes in PoReHis and stimulus to left ventricular activation time.